Invoke call upon the beautiful names of Allah - Sharifah Nadirah 1994-; Nur Syafiqah (WhiteCoat Group Sdn. Bhd., 2022)
We present to you a poetry of the 99 names of Allah, written with love and joy. Crafted with warmth and tenderness. Sculptured with delight and fondness. May each poem reaches your heart with peace and tranquility.